Four-week "live high, train high and low" period at simulated altitude increased hemoglobin mass but not maximal oxygen uptake in Cross-Country skiers - Kettunen, O.; Leppävuori, A.; Mikkonen, R.; Peltonen, J.; Nummela, A.; Perätalo, M.; Wikström, B.; Linnamo, V. (Book of Abstracts. 4th Nordic Winter Sports Conference "Performance in snow sports: Translating science into practice" 3rd-4th October, 2022, Mid Sweden University, Campus Östersund, Sweden, 2022)
Aim To clarify whether four weeks of "live high, train high and low" (LHTHL) at simulated altitude influenced hemoglobin mass (Hbmass) and maximal oxygen uptake (VO_2max).